DOMAIN HASIL PEMBELAJARAN BERASASKAN KERJA (PBK) DALAM LATIHAN INDUSTRI TERHADAP PELAJAR POLITEKNIK BERDASARKAN PERSEPSI PEMBIMBING - Zakaria, Normah; Khamis, Arasinah; Amran, NorIzzati Aqirah (Online Journal for TVET Practitioners, 2018)
The Ministry of Higher Education Malaysia has been striving to introduce a new education system in Polytechnics to ensure our education system to achieve a commendable level. Education system have just introduced is known as Work-Based Learning (WBL). The learning aims to provide students who are highly skilled. Therefore, this study aimed to identify the level of WBL outcome and dominant domain of WBL outcome against WBL Polytechnic students Diploma Electronic Engineering (Medical). This study has used quantitative methods involving descriptively questionnaire as an instrument. The respondent consists of 52 people cooperating industrial Advance Pact Sdn.Bhd which manage medical electronic machine at government hospitals around Johor. Quantitative data was analysed descriptively using score mean and standard deviation to see WBL outcome and also dominant domain of WBL outcome against WBL Polytechnic students Diploma Electronic Engineering (Medical). The results of the study found the level of WBL outcome is high and dominant domain of WBL outcome is the domain of professionalism. Overall, Polytechnic students need to have domain of WBL outcome according to the programmes provided at Polytechnic in order to working in the industry later.